Influência de elementos climáticos no desenvolvimento do oídio do cajueiro - Holanda, Antonia Fabiana Pinto de (2024)
Among the phytosanitary problems of cashew trees, powdery mildew is considered the most important disease. Although it is known that there are two causal agents: Erysiphe necator which attacks mature leaves and E. quercicola which attacks young tissues, such as maturis and inflorescences, this species being the most harmful to the crop, there is a lack of information on the behavior of the fungus. in response to climatic factors such as relative humidity, light, and temperature as well as in response to different inoculum sources. Considering the dependence on the primary inoculum in the fungal infection cycle, as well as the climatic elements in powdery mildew epidemics, experiments were carried out to evaluate the effect of temperature, relative humidity, and light influencing the development of the disease.In the first experiment, the objective was to evaluate the behavior of E. quercicola obtained from different sources of inoculum, new maturi, old maturi, necrotic maturi, leaf, and inflorescence under different humidity and temperature conditions. The conidia extracted from each inoculum source were subjected to climatic conditions of 0, 30, 50, 70, and 100% relative humidity at a temperature of 23ºC under a 12h photoperiod. Relative humidity does not interfere with germination and appressoria formation, unlike inoculum sources, with inflorescences being those that obtained more viable inoculums, while old maturis presented less viable conidia. When the interaction between temperature and the light spectrum was analyzed, it was found that the spectra corresponding to the colors green and red induced greater germination and formation of appressoria. While blue light suppressed the development of conidia.Furthermore, the factors temperature and photoperiod influence the behavior of conidia, with a temperature of 23ºC and a photoperiod of 12h being the ideal levels within each factor to increase the germination and appressorium formation of E. quercicola conidia. To study the influence of climatic elements on the development of powdery mildew on cashew trees, experiments were carried out under controlled conditions and in the field. In the laboratory and using the leaf disc methodology, the effect of three color spectra (red, green, and blue) x three photoperiods (17h, 12h, and 7h) x two temperatures (17ºC and 23ºC) with three repetitions each and a control. Four leaf discs were placed in each Petri dish and incubated in BODs with 15W fluorescent lamps and an average light intensity of 0.59 μmol.m-2.s-1. The number of conidia produced was evaluated.In the field, powdery mildew developed on cashew seedlings was evaluated under the influence of light using shades with meshes of 30%, 50%, and 70% light exposure, in addition to 0% light exposure using matte black plastic bags, and 100%, where the plants were completely exposed to the sun inside the cages. The experiment was conducted in a completely randomized design in a factorial scheme with 5 light intensity levels. In each cage, 5 seedlings in the juvenile stage of BRS - 189 clones were placed. It was found that E. quercicola in interaction with cashew leaf discs develops better at a temperature of 23ºC and in the 7h photoperiod, and almost all color spectrums, except the blue light spectrum, which presented the lowest average number of conidia.cm-2. Furthermore, it was found that the severity of the disease and sporulation worsened from 4 DAI to 20 DAI and at lower light intensities, that is, lower light exposures, highlighting the treatment of 0% light with an illuminance of 0 .0014 - 0.0049μmol.m-2.s-1.